The Rift valley fever - ΣΕΪΜΕΝΗΣ Α.; ΣΤΟΦΟΡΟΣ Ε. (Journal of the Hellenic Veterinary Medical Society, 2019)
An overall aspect of the Rift Valley Fever on sensitive animals and humans is exposed. Beside the sanitary measures, not always effective, the disease could be faced through preventive vaccinations only. According the geographic evolution of the R.V.F. during the past years, the threat for an eventual extension beyond the Nile Delta area (where it broke out three years ago). if the favourable conditions for such an extension should be created, could not be excluded.